Promising Effects of Neurorestorative Diets on Motor, Cognitive, and Gastrointestinal Dysfunction after Symptom Development in a Mouse Model of Parkinson's Disease - Perez-Pardo, Paula; de Jong, Esther M.; Broersen, Laus M.; van Wijk, Nick; Attali, Amos; Garssen, Johan; Kraneveld, Aletta D. (Frontiers in Aging Neuroscience, 2017)
Parkinson’s disease (PD) is characterized by the progressive degeneration of dopaminergic nigrostriatal neurons, with reductions in the function and amount of dopaminergic synapses. Therefore, synapse loss and membrane-related pathology provide relevant targets for interventions in PD. We previously showed the beneficial preventive effects of a dietary intervention containing uridine and DHA, two precursors for membrane synthesis, in the intrastriatal rotenone model for PD. Here, we examined the therapeutic potential of the same dietary intervention on motor, cognitive and gastrointestinal symptoms. In addition, we tested the effects of an extended nutritional formula based on the same precursors plus other nutrients that increase membrane phospholipid synthesis as well as prebiotic fibers. C57BL/6J mice received a unilateral rotenone injection in the striatum. Dietary interventions started 28 days after surgery, when motor-symptoms had developed. Readout parameters included behavioral tasks measuring motor function and spatial memory as well as intestinal function and histological examination of brain and gut to assess PD-like pathology. Our results show that rotenone-induced motor and non-motor problems were partially alleviated by the therapeutic dietary interventions providing uridine and DHA. The extended nutritional intervention containing both precursors and other nutrients that increase phospholipid synthesis as well as prebiotic fibers was more effective in normalizing rotenone-induced motor and non-motor abnormalities. The latter diet also restored striatal DAT levels, indicating its neurorestorative properties. This is the first study demonstrating beneficial effects of specific dietary interventions, given after full development of symptoms, on a broad spectrum of motor and non-motor symptoms in a mouse model for PD.